2011
DOI: 10.1542/peds.2011-0603
|View full text |Cite
|
Sign up to set email alerts
|

Urinary N-Terminal B-Type Natriuretic Peptide Predicts Severe Retinopathy of Prematurity

Abstract: UNBCR might hold promise to reduce unnecessary eye examinations by timely and accurate identification of infants at risk of severe ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 25 publications
0
31
1
1
Order By: Relevance
“…Subsequently, Celik et al (13) noted similar results and notified that urinary NT-ProBNP levels may help clinicians to determine the effects of hs-PDA on the clinical status of preterm infants. Czernik et al (30) published higher urinary NT-ProBNP levels in preterm neonates who further developed retinopathy of prematurity. Although we aimed to elucidate the predictive potential of urinary NT-ProBNP in the determination of "severity" in childhood LRTI, we could not demonstrate any relation.…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, Celik et al (13) noted similar results and notified that urinary NT-ProBNP levels may help clinicians to determine the effects of hs-PDA on the clinical status of preterm infants. Czernik et al (30) published higher urinary NT-ProBNP levels in preterm neonates who further developed retinopathy of prematurity. Although we aimed to elucidate the predictive potential of urinary NT-ProBNP in the determination of "severity" in childhood LRTI, we could not demonstrate any relation.…”
Section: Discussionmentioning
confidence: 98%
“…In VLBWI, N‐terminal‐probrain natriuretic peptide (NT‐proBNP) is correlated with the echocardiographic markers of a hemodynamically significant patent ductus arteriosus (HsPDA) and its response to treatment . Studies of the role of NT‐proBNP in other situations are limited, but preliminary data suggest that NT‐proBNP can be a useful marker of other major morbidities, such as intraventricular hemorrhage (IVH), retinopathy and BPD …”
Section: Introductionmentioning
confidence: 99%
“…3,4 In VLBWI, N-terminalprobrain natriuretic peptide (NT-proBNP) is correlated with the echocardiographic markers of a hemodynamically significant patent ductus arteriosus (HsPDA) [5][6][7][8] and its response to treatment. [9][10][11][12][13][14] Studies of the role of NT-proBNP in other situations are limited, but preliminary data suggest that NT-proBNP can be a useful marker of other major morbidities, such as intraventricular hemorrhage (IVH), 14 retinopathy 15 and BPD. [16][17][18] VLBWI with established BPD have higher NT-proBNP levels than healthy infants, and the degree of elevation is correlated with disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…Successfully identifying a noninvasive biomarker for the development of ROP would have significant financial, family and infant benefits. Urinary NTproBNP appeared promising in pilot work (8), and in a larger population of relatively immature infants (<30 + 0 weeks of gestation (12). However, in the present study performed in more mature infants who are still judged at risk of ROP by current screening criteria, a relationship between urinary NTproBNP and the development of ROP has not been demonstrated.…”
Section: Discussionmentioning
confidence: 54%
“…Concentrations of NTproBNP in blood parallel those in the urine, making noninvasive measurement possible . In a single‐centre pilot study, we showed that urinary NTproBNP/creatinine ratios (UNBCR) in the first month were significantly elevated in preterm infants who developed severe ROP, compared to controls . To further assess the predictive power of urinary NTproBNP concentrations and UNBCR during the first month of life to allow early identification of infants at high or low risk of severe ROP, we conducted a prospective observational study (REDEXAM, REDucing Eye EXAMinations in preterm infants) in neonatal intensive units in eight European and Middle East countries .…”
Section: Introductionmentioning
confidence: 99%